Prenatal Methamphetamine Exposure, Home Environment, and Primary Caregiver Risk Factors Predict Child Behavioral Problems at 5 Years. (18th January 2013) - Twomey, Jean; LaGasse, Linda; Derauf, Chris; Newman, Elana; Shah, Rizwan; Smith, Lynne; Arria, Amelia; Huestis, Marilyn; DellaGrotta, Sheri; Roberts, Mary; Dansereau, Lynne; Neal, Charles; et al.
<x xml:space="preserve">Abstract</x> This study investigated the prospective association between prenatal methamphetamine (MA) exposure and child behavioral problems at 5 years while also examining the home environment at 30 months and several primary caregiver (PC) risk factors. Participants were 97 MA‐exposed and 117 comparison children and their PCs enrolled in the Infant Development, Environment and Lifestyle Study. Hypotheses were that child behaviors would be adversely impacted by (a) prenatal MA exposure, (b) home environments that provided less developmental stimulation and emotional responsiveness to the child, and (c) the presence of PC psychological symptoms and other risk factors. Prenatal MA exposure was associated with child externalizing behavioral problems at 5 years. Home environments that were more conducive to meeting children's developmental and emotional needs were associated with fewer internalizing and externalizing behavioral problems. Independent of prenatal MA exposure, PC parenting stress and psychological symptoms were associated with increased child behavioral problems. Findings suggest prenatal MA exposure may contribute to externalizing behavioral problems in early childhood and the importance of considering possible vulnerabilities related to prenatal MA exposure in the context of the child's caregiving environment.